IDENTIFIKASI MARKA GEN KETAHANAN HAWAR DAUN BAKTERI PADA GALUR PADI INTRODUKSI DAN GALUR DIHAPLOID - Ovi Prasetya Winandari; Aris Tjahjoleksono .; Dwinita Wikan Utami (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
Identification marker of bacterial leaf blight (BLB) gene resistance on introducted and dihaploid rice germplasm. Bacterial leaf blight (BLB), caused by bacterial pathogen Xanthomonas oryzae pv. oryzae (Xoo), is one of the most devastating diseases in rice. The use of BLB-resistant rice varieties is one of the most efficient ways to protect rice from this disease. BLB-resistant varieties can be produced through the breeding program by using the diverse rice germplasm. The objective of this research was to identify BLB resistance gene on 37 introducted and dihaploid rice lines derived from wide genetic background double crossing from local rice : IR54/Parekaligolara and Bio110/Markuti, by using the molekular markers. As control plant used 23 differential varieties (monogenic lines/IRBB) and TN1 (susceptible). All plants tested were inoculated by 3 selected dominant BLB races (Race III, IV dan VIII). The selected of 19 polymorphism molecular markers used to identify the BLB resistance genes on rice lines tested. The result of this research showed that 4 rice lines were resistance to all BLB races tested. Three molecular markers were specific associated with resistant gene to Race III (Xa7-STS40, Xa1-STS14 and Xa4-STS50); Race IV (Xa1-STS5, Xa4-STS50 and Xa26-STS1), and Race VIII (Xa21-STS6, Xa7-RM20590 and Xa7-STS40). These markers could be utilized for the selection process the developmen of BLB resistance rice lines breeding program.